THE COMMUNICATION OF FORTUNE TELLERS’ CREDIBILITY ON ONLINE PLATFORMS - Pattarasriapirom, Nongnart; Thonglert, Grit (Journal of MCU Nakhondhat, 2026)
This research aimed to examine the core content themes employed by fortune tellers in their communication, the communication strategies used to establish credibility, and user-generated content (UGC) created on online platforms. The concepts and theories utilised in this study included Berlo’s Communication Model, Credibility Theory, Identity Theory, Rhetorical Theory, Semiotic Approaches, the concept of UGC, and Media Dependency Theory. This study adopted a qualitative research approach through content analysis of online platform content from three fortune-teller pages. A total of 540 online content items were collected between January 1, 2025, and June 30, 2025, and were analyzed through textual analysis and communication interpretation. The findings revealed that: 1) The content communicated by fortune tellers on online platforms consisted of horoscope and fortune prediction, worship rituals, auspicious date and time selection, recommendations of spiritual tourism destinations, amulet rental services, physiognomy, feng shui, and signature design; 2) The communication strategies used to establish credibility included the encoding of distinctive verbal language, the use of unique body language, the use of distinctive clothing codes, the rational linkage between astrological movements and individual behavior, the use of repetition techniques to convey expertise, the use of symbolic backgrounds to reinforce narratives, and the creation of trust through personalized signature designs; and 3) UGC included expressions of appreciation and religious blessings such as “Sadhu”, the sharing of photographs related to participation in rituals, exchanges of opinions with other users, the sharing of experiences resulting from the use of amulets, and the embedding of product advertisements within comments. These practices reflected the active participation of followers within online media spaces.